Outcomes and risk factors for ERCP-related complications in a predominantly black urban population. Issue 1 (17th September 2020) - Kwak, Nathaniel; Yeoun, Daniel; Arroyo-Mercado, Fray; Mubarak, Ghassan; Cheung, Derrick; Vignesh, Shivakumar
Abstract : Objective: There is a lack of literature on postendoscopic retrograde cholangiopancreatography (ERCP) complications in predominantly black urban populations of low socioeconomic status. The aim of this study was to determine the incidence and predictors of post-ERCP complications in this patient population. Design: Retrospective review of ERCP cases performed at two hospitals from 2007 to 2017 was performed. The categories of complications evaluated were overall complications, severe or fatal complications, pancreatitis, bleeding, infection, perforation and cardiopulmonary events. Predictors of complications were determined by univariate analysis. Results: A total of 1079 ERCP procedures were reviewed. There were 106 complications (9.8%). Twenty-one were severe (1.9%) and 20 were fatal (1.9%). Both post-ERCP pancreatitis (PEP) and post-ERCP bleeding occurred in 18 patients (1.7%) each. Risk factors for overall complications were male sex (OR 1.54), ASA grade IV or V (OR 2.19), prior history of PEP (OR 6.98) and pancreatic duct stent placement (OR 2.75). Those who were ASA grade III or lower (OR 0.4) or who underwent biliary stone extraction (OR 0.62) had fewer complications. PEP was more likely in those with a prior history of PEP (OR 37.6). Those with a suspected or known biliary duct stone had less frequent pancreatitis (OR 0.32). Post-ERCP bleeding was more likely in the presence of cholangitis (OR 8.72). Conclusion: Outcomes of ERCP in a predominantly black urban population demonstrate a lower incidence of PEP and all-cause mortality compared with historical data reported in the general population. Potential risk factors for post-ERCP complications were identified but require larger studies for validation.